THE SOCIO-CULTURAL WORK CARRIED OUT IN THE BUKHARA REGION IN THE 50S AND 60S OF THE 20TH CENTURY AND THEIR ACTIVITIES (Центральноазиатский журнал образования и инноваций, 2025)
This article is aimed at highlighting the work carried out in the socio-cultural sphere and their activities in the Bukhara region in the 1950s - 1960s of the 20th century. It analyzes the work carried out in the post-war years on the organization of educational, healthcare, cultural and educational institutions, namely the construction of houses of culture, clubs, theaters, museums, libraries and household service facilities and their activities. In the process of research, the work carried out in the field of education and healthcare in the Bukhara region, as well as the fact that it has become a center for organizing houses of culture, clubs, amateur circles and mass cultural events, and the state of ideological and educational work in the activities of theaters and museums are studied. At the same time, the network of libraries is expanding, cinemas and summer cinemas, the sphere of household services - hairdressers, canteens and teahouses - is studied, their important role in improving the living conditions of the population and ensuring their participation in cultural life. Also, problems in some areas are analyzed from a critical and historical point of view.